The Athlete's Personal Authenticity as a Resource of Mental Well-Being in a Crisis of Coping with Sport Injury - Bochaver, K.A.; Desyatnikova, A.V.; Zyazina, N.A. (Sovremennaâ Zarubežnaâ Psihologiâ, 2025)
The article presents an overview of modern foreign studies on the well-being of professional athletes during the period of coping with the crisis associated with sport injury. It is indicated that sports injury has not only signs of damage to the body, but also triggers specific deep processes, including combined distress, violation of psychological well-being, inability to plan and implement professional goals. To cope with them, an injured athlete needs a wide range of internal mental resources, and in their context, personal authenticity is of particular importance. The approaches to understanding this phenomenon are analyzed, and studies on related topics are presented that reveal the psychological potential of authenticity in preserving and strengthening psychological well-being. On the model of sports injury, the prospect of a special successful rehabilitation through the implementation of internal growth associated with injury (SIRG) is considered. The problems and prospects of further research are outlined, and a vision is given of the wide application of the described mechanisms in the work related to the recovery of patients and their psychological well-being. В статье представлен обзор современных зарубежных исследований, посвященных благополучию (well-being) профессиональных спортсменов в период преодоления кризиса, связанного с получением травмы. Указывается, что спортивная травма обладает не только признаками повреждения организма, но и запускает специфические глубинные процессы, включая комбинированный дистресс, нарушение психологического благополучия, невозможность планировать и реализовывать профессиональные цели. Для их преодоления травмированный спортсмен нуждается в широком ряде внутренних ресурсов, и в их контексте особое значение приобретает личностная аутентичность (personal authenticity). Анализируются подходы к пониманию этого феномена, приводятся исследования по смежным темам, раскрывающие психологический потенциал аутентичности в сохранении и укреплении психологического благополучия. На модели спортивной травмы рассматривается перспектива особой благополучной реабилитации путем реализации внутреннего роста, связанного с травмой (sport injury related growth). Обозначаются проблемы и перспективы дальнейших исследований, дается видение широкого применения описанных механизмов в работе, связанной с восстановлением пациентов и их психологическим благополучием.